UM radio interface in GSM - Mohd Arshad, Nor Aziah (2000)
The Global System for Mobile communication (GSM) is a digital cellular communications system initially developed in an European context which has rapidly gained acceptance and market share worldwide. A GSM network consists of a number of-well defined open interface. The interface between mobile (MS) and Base Transceiver Station (BTS) is called air interface or Um interface Here Mobile Radio Analyzer (MA10) is used to see the activities involved between MS and BTS. Simulation programming using Visual Basic is used to simulate data from MA10. This project presents and approach on how to locate Mobile Station using triangulation solution.